Unexpected CEO death and its consequences for firm performance - Sincerre, Bianca Piloto (2021)
It is generally recognized in the finance and accounting literature that the board of directors and the chief executive officer (CEO) play a key role in business operations and creating value for the company's shareholders. The inherent question is that when there is a sudden turnover, such as the unexpected death of a CEO, how does the company maintain its results and what is the impact of an unexpected death on the company's performance. The main motivation of this study is precisely to understand these questions from three different perspectives: i) the impact of an unexpected death on the company's value; ii) the impact of an unexpected death on the company's cost of capital; and iii) the impact of an unexpected death on the stock price reaction. The first chapter deals with the fundamental question of the study: the impact on firm value caused by the unexpected death of a CEO, and as a result, a quick and sudden change in installing a new CEO. In a sample composed for U.S. public company CEOs who died unexpectedly while in office between 1950 and 2018, I identified 265 CEOs who died suddenly. The results show that the sudden CEO death has a negative impact on Tobin´s Q. The second and third chapters complement the first to understand what other variables could explain this drop in the company's value after an unexpected CEO death. In Chapter 2 I use sudden CEO death as a natural experiment to analyze its impact on the implied cost of equity capital. The empirical results show that the implied cost of equity capital is positively associated with unexpected CEO death, after controlling for firm performance measures and risk factors. Chapter 3 tries to understand the effect of the unexpected death of a CEO in the short term, through an event study analyzing stock price reactions. The second analysis it is to identify which individual CEO characteristics may be related to the stock price reaction. I show that market reactions to these events in U.S. public firms have had a negative impact in terms of stock price reactions over time. I also find that CEO age has a positive effect on market reaction after an unexpected death, indicating a possible entrenchment, while when an older CEO is changed suddenly, it is well received by the market, and as a result there is a positive impact on the stock price reaction.